Upaya Deteksi Dini Kanker Prostat Melalui Pemberdayaan Tenaga Kesehatan Posyandu Lansia Dinkes Kota Banjarmasin - Eka Yudha Rahman; Roselina Panghiyangani; Nia Kania; Nika Sterina Skripsiana (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
Prostate cancer is one of the malignancies in men, the second most common cancer, and the sixth leading cause of death in men worldwide. The life expectancy of men in Banjarmasin City is increasing every year. As the elderly increase, the risk of prostate cancer also increases. Prostate Cancer Early Detection training is needed for health workers at Posyandu Lansia (Integrated Health Care Center for the Elderly) under the work area of Banjarmasin Health Office. The implementation of community service activities in the form of training on early detection of prostate cancer for health workers and cadres of Posyandu for the elderly in the Banjarmasin Health Office work area consists of 2 days of implementation, on 2 and 3 August 2022, at the Roditha Hotel Banjarmasin. Participants in this activity were 88 health workers and Posyandu cadres in the Banjarmasin City Health Office work area. Activities are carried out offline by implementing health protocols. This training activity includes a pretest, a presentation of training material by two speakers from FK ULM, a demonstration of the digital rectal examination technique (rectal toucher), discussion, response, and post-test. The success of this activity can be seen from the increase in knowledge (pretest average score of 35.88 and post-test of 76.18) and skills of health workers and Posyandu cadres in the Banjarmasin City Health Office work area regarding early detection and prevention of prostate cancer.